Quality of life research: interview with Professor Robert Cummins - Robert Cummins; Paraskevi Theofilou (Health Psychology Research, 2013)
Health-related quality of life (HRQOL) is a fundamental concept in the field of clinical medicine and has been studied during the last years by psychologists, sociologists, economists and managers. The concept of HRQOL includes those aspects of overall QOL that can be indicated to have an impact on patients’ health, either physical or psychological. Concerning the individuals, this incorporates physical and mental health cognitions, including sociodemographic factors, sexual functioning, fatigue, sleep disorders and functional status. One of the most eminent experts in the world in the field of QOL is Prof. Robert Cummins [Professor of Psychology at Deakin University in Australia (School of Psychology, Deakin University, 221 Burwood Highway, Victoria 3125 Melbourne, Australia. E-mail: robert.cummins@deakin.edu.au)] who kindly accepted to answer our questions in the con- text of this special edition.